Use of psychotropic medications by caregivers of elderly patients with dementia: is this a sign of caregiver burden? - Camargos,Einstein Francisco (2012)
This study evaluated the consumption of psychotropic medications by caregivers of elderly patients with or without dementia. This was a cross-sectional study conducted at all geriatric units in Brasília, Brazil, during a two-month period. Structured interviews were performed with 311 caregivers of people with or without dementia and they completed questionnaires. Among the caregivers, 196 (63%) were caregivers of patients with dementia and 115 (37%) were caregivers of patients without dementia. Forty-four caregivers (14.1%) were taking psychotropic drugs (benzodiazepines or antidepressants), and this usage was more frequent among caregivers of patients with dementia (p<0.01). Twenty-two caregivers of patients with dementia (11.4%) had used sleeping pills after beginning care, compared with only five (4.3%) caregivers of patients without dementia (p<0.01). In conclusion, this study found that caregivers of patients with dementia took psychotropic drugs (benzodiazepines and antidepressants) more frequently than the ones of patients without dementia.